Considerations for introducing a cloud service in health informatics: user experience monitoring of information systems - Welander, Melissa (My University, 2021)
This thesis will show concrete examples about how user experience monitoring will improve security of health information systems, patient safety, efficiency, and ease of use. This thesis will prove how the current EMR systems that are stand alone in nature lack the ability of advanced error monitoring capabilities. As part of this research, I will demonstrate with detailed interviews and data collection surveys how automated user monitoring systems improve data record accuracy consistently. Key terminology to Electronic Medical Records (EMR’s) and the usability of cloud computing software solutions will be defined. EMR’s are the primary software used in hospitals for charting patient information and this research focuses on the summarization of key information to the history of healthcare technologies and their functionalities. Usability testing, cloud computing, and how security and trust are affecting the adoption of cloud-based services will also be discussed in more detail. Along with the importance of market research, how to create buyer personas, and what drives their need to buy. The study was conducted in collaboration with Adusso Ltd. in Helsinki, Finland to gain better understanding about what motivates hospital IT departments to buy and the main issues with EMR systems. In collaboration with Adusso we investigated a use case example of their existing customer Apotti leveraging the user error reduction and cost saving benefits they experienced after deploying Adusso’s UX2play system. We sought answers to these topics using semi-structured interviews and analyzing our customer profiles. We found that UI layout, interoperability, and the number of clicks that nurses spend in the EMR are major issues that most EMR systems have. This implies that companies using EMR’s should implement user monitoring to pinpoint the issues they do have so that they can be fixed and the work of physicians and clinicians can be improved.
Keywords: EMR, EHR, Optimization, Usability Research, User Experience Monitoring, Market Research, Cloud Computing, SaaS